Effective collaborative learning from Chinese students' perspective: a qualitative study in a teacher-training course. Issue 2 (17th February 2023) - Lee, Wincy Wing Sze; Yang, Min
ABSTRACT: This paper examines undergraduate students' perceptions of when and how active learning and engagement were supported by group-based collaborative learning. Collaborative learning is a prevalent constructivist approach that has been promoted for its capability of assisting students' shared knowledge construction. Existing research has, nonetheless, pointed towards social-cultural barriers to students' participation in collaborative learning, particularly in Eastern societies. This study explored students' perceptions of collaborative learning in group tasks during a 12-week course. Interviews revealed key themes regarding students' perspectives on what effective and meaningful collaborative work in classrooms meant to them, and how and why collaborative work motivated and engaged them. Survey findings, which helped to triangulate interview findings, showed that students' experiences of collaborative learning were supported by key elements of constructivist learning environments. Implications are derived for effective pedagogical design and theorization of collaborative learning in higher education.